Adjectives in English French and Berber Kabyle: A Contrastive Study - Hocine, Nacira (Journal of Human Sciences, 2007)
The aim of the present article is to compare and contrast the syntactic category of adjectives in three different languages: English, French and Berber Kabyle in order to delimit whether the members of the word class adjective are the same in the three languages, whether they share the same characteristics, whether they are formed through the same syntactic functions. Our study comprises a section where the three languages under discussion will be introduced as well as the status of the word class adjective in the three languages. We will devote a section to discuss the syntactic category of nouns since the latters have a direct syntactic relationship with adjectives and they form an imposing part in our work. We will also devote a section to the definition of adjectives, their origins and formation processes, their characteristics and their syntactic functions. A last section will be devoted to the comparison system in the three languages.